Problem Solving in Geometry Teaching for Pre-service Mathematics Teacher Students from a Computational Thinking Perspective - Jupri, Al; Usdiyana, Dian; Gozali, Sumanang Muhtar (UNNES JOURNAL, 2024)
Computational thinking and problem-solving skills are necessary for the future careers of pre-service mathematics teacher students in the 21st century. This study aims to analyse problem-solving activities in geometry teaching and corresponding assessment for pre-service mathematics teacher students from a computational thinking perspective. To do so, we carried out a qualitative case study through teaching and learning observations involving 41 pre-service mathematics teacher students from one of the state universities in West Java, Indonesia. In this study, 6 x 50 minutes of geometry teaching were observed, and written work containing problem-solving processes retrieved from the formative assessment was analysed from the computational thinking perspective. The results showed that two types of problem-solving activities are identified from the teaching and learning processes and the corresponding assessment, i.e., problem to find and problem to prove. We view that a problem to prove can typically be considered as a structured problem to find. Both types of problems can be fruitfully analysed using Polya’s problem-solving strategy from the computational thinking perspective. For future research, we recommend investigating each type of problem using more specific characteristics of computational thinking. Keterampilan berpikir komputasi (computational thinking) dan pemecahan masalah diperlukan untuk karir masa depan mahasiswa calon guru matematika di abad ke-21. Penelitian ini bertujuan untuk menganalisis aktivitas pemecahan masalah dalam proses pembelajaran geometri dan asesmennya untuk mahasiswa calon guru matematika dari perspektif berpikir komputasi. Untuk itu, kami melakukan studi kasus kualitatif melalui observasi proses pembelajaran yang melibatkan 41 mahasiswa calon guru matematika dari salah satu universitas negeri di Jawa Barat, Indonesia. Dalam penelitian ini, kami mengobservasi pembelajaran geometri untuk calon guru matematika selama 6 x 50 menit, dan hasil tes tertulisnya yang berisi proses pemecahan masalah yang dianalisis dari perspektif berpikir komputasi. Hasil penelitian menemukan adanya dua jenis tipe pemecahan masalah, yang diidentifikasi dari pengamatan proses pembelajaran dan penilaian formative, yaitu masalah tipe menemukan dan masalah tipe membuktikan. Kami memandang bahwa masalah tipe membuktikan sebagai masalah terstruktur dari tipe menemukan. Kedua tipe masalah tersebut dapat dianalisis dengan baik menggunakan strategi pemecahan masalah Polya dari perspektif berpikir komputasi. Untuk penelitian mendatang, kami merekomendasikan untuk menelaah lebih lanjut setiap tipe masalah dengan menggunakan karakteristik berpikir komputasi yang lebih spesifik.